PENGARUH LATIHAN MENGGUNAKAN BOLA KESEHATAN (MEDICINE BALL) TERHADAP HASIL EXPLOSIVE POWER OTOT LENGAN DAN BAHU SISWA EKSTRAKULIKULER BOLA BASKET SMA NEGERI 11 PEKANBARU - Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The problem in this study is the authors were interested to know the effect of exercise using medicine ball on the result of explosive power arm and shoulder muscles students extracurricular basketball SMA 11 Pekanbaru. The purpose of this study was to determine the effect of exercise using medicine ball on the result of explosive power arm and shoulder muscles students extracurricular basketball SMA 11 Pekanbaru. The population in this study were students in extracurricular basketball SMA 11 Pekanbaru many as 12 students. The research sample using totalsampling ie sampling technique when all members of the population used as a sample. The data is taken directly by researchers or visible / carried out directly by the researchers, the results of pre-test and post-test given to students in extracurricular basketball SMA 11 Pekanbaru. Data analysis by using pre-test and post test one group design. Based on the research that there are significant medicine ball exercises for the arm and shoulder muscle power in students extracurricular basketball SMA 11 Pekanbaru.Keywords: Exercise Medicine Ball, explosive power arm and shoulder muscles